2022
DOI: 10.1155/2022/9492056
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Ultrasound Diagnosis of Thyroid Nodules Based on Artificial Intelligence-Assisted Diagnostic Technology: A Systematic Review and Meta-Analysis

Abstract: Background. Ultrasonography (US) is the most common method of identifying thyroid nodules, but US images require an experienced surgeon for identification. Many artificial intelligence (AI) techniques such as computer-aided diagnostic systems (CAD), deep learning (DL), and machine learning (ML) have been used to assist in the diagnosis of thyroid nodules, but whether AI techniques can improve the diagnostic accuracy of thyroid nodules still needs to be explored. Objective. To clarify the accuracy of AI-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…It was more objective on the segmentation results than manually initializing contours.AI can extract and quantify critical image information, transforming image diagnostics from subjective qualitative tasks into objective quantitative analysis. 26 Several recent studies show that it has diagnostic performance comparable to that of experienced radiologists. [27][28][29][30][31] Such a tool could offer great advantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was more objective on the segmentation results than manually initializing contours.AI can extract and quantify critical image information, transforming image diagnostics from subjective qualitative tasks into objective quantitative analysis. 26 Several recent studies show that it has diagnostic performance comparable to that of experienced radiologists. [27][28][29][30][31] Such a tool could offer great advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, AI‐SONIC is based on automatic initial contour extraction and utilizes proper algorithms to obtain initial contours before applying active contour models to thyroid nodule segmentation. It was more objective on the segmentation results than manually initializing contours.AI can extract and quantify critical image information, transforming image diagnostics from subjective qualitative tasks into objective quantitative analysis 26 . Several recent studies show that it has diagnostic performance comparable to that of experienced radiologists 27–31 .…”
Section: Discussionmentioning
confidence: 99%
“…The paper also proposed future trends and challenges in the field and perspectives of computer-aided analysis to improve the efficiency of future methods for thyroid cancer diagnosis. In Ludwig et al (2023) and Xue et al (2022) the particular focus is on the usefulness of AI in ultrasonography for the diagnosis and characterization of thyroid cancer. Sorrenti et al (2022) also report an overview of the state of the art regarding AI implementation for thyroid nodule ultrasound characterization and cancer.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, they proposed that the experienced radiologists may still have an advantage over AI algorithms in the real-time diagnostic process [ 68 ]. In the meta-analysis by Yu et al patients were grouped by age, and the analysis results showed that AI-assisted diagnostic techniques had higher diagnostic performance in subjects with an average age of < 50 years [ 69 ]. However, it is still important to note that benign nodules detected by ultrasound are likely to be histopathologically malignant, so the AI algorithms should not be expected to be foolproof.…”
Section: Introductionmentioning
confidence: 99%